A Study on Sociability of Higher Secondary Students - S. , Sermathangam; H. , Deepa (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates about the sociability of higher secondary school students with reference to some background variables such as gender, locality, medium of study, etc. The survey method is used for collecting data for this study. Random sampling technique was used. Data gathered from 250 higher secondary students, from which 125 are males and 125 are females. The results indicated that there is significant difference between boys and girls in their sociability. While comparing the mean scores of male (mean=64.9281) and female (mean=68.1261), the female students have more sociability than the male students. This may be due to the fact that the female students can be easily interact with others. They are more sociable with others. These results highlight the importance of attending to sociability during early adolescence in the school environment make the students more sociable.